JOB STRESS, JOB SATISFACTION, WORK ENVIRONMENT: EFFECTS ON ORGANIZATIONAL COMMITMENT AND IMPACT ON TURNOVER INTENTION - Purnomo, Indra; Bernarto, Innocentius (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. The purpose of this study was to determine then influences of organizational commitment toward turnover intention, moreover the effects of job stress, job satisfaction, and work environment on organizational commitment was also observed, and finally the influence of job stress and work environment had on job satisfaction. Data collection was conducted via electronic questionnaire on 268 hospital employees. Data analysis was done using partial least square-structural equation modeling technique (PLS-SEM) using program software SmartPLS 3.0. Results from this study showed that organizational commitment had negative effects on turnover intention, meanwhile organizational commitment was negatively influenced by job stress and positively influenced by job satisfaction and work environment, finally job satisfaction was negatively influenced by job stress and positively influenced by work environment. This study aims to contribute to the understanding of employee turnover dynamics and give understanding on the underlying factors that affects turnover intention. Given the results derived from this study, it is recommended for any organizations stakeholder to improve employee’s commitment to control turnover, by boosting employee’s satisfaction and work condition, as well as reducing their stress. Abstrak.  Tujuan dari penelitian ini adalah untuk mengetahui pengaruh komitmen organisasi terhadap turnover intention, selain itu juga diamati pengaruh stres kerja, kepuasan kerja, dan lingkungan kerja terhadap komitmen organisasi, dan terakhir pengaruh stres kerja dan lingkungan kerja terhadap pekerjaan. kepuasan. Pengumpulan data dilakukan melalui kuesioner elektronik pada 268 pegawai rumah sakit. Analisis data dilakukan dengan menggunakan teknik partial least square-structural equation modeling (PLS-SEM) dengan menggunakan perangkat lunak program SmartPLS 3.0. Hasil dari penelitian ini menunjukkan bahwa komitmen organisasi berpengaruh negatif terhadap niat berpindah, sedangkan komitmen organisasi dipengaruhi secara negatif oleh stres kerja dan dipengaruhi secara positif oleh kepuasan kerja dan lingkungan kerja, terakhir kepuasan kerja dipengaruhi secara negatif oleh stres kerja dan dipengaruhi secara positif oleh lingkungan kerja. Penelitian ini bertujuan untuk berkontribusi pada pemahaman dinamika turnover karyawan dan memberikan pemahaman tentang faktor-faktor mendasar yang mempengaruhi niat turnover. Berdasarkan hasil penelitian ini, disarankan bagi setiap pemangku kepentingan organisasi untuk meningkatkan komitmen karyawan dalam mengendalikan turnover, dengan meningkatkan kepuasan dan kondisi kerja karyawan, serta mengurangi stres mereka.